2013 IEEE Congress on Evolutionary Computation 2013
DOI: 10.1109/cec.2013.6557985
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary hybrid computation in view of design information by data mining

Abstract: Design Informatics has three points of view. First point is the effident exploration in design space using evolu tionary computation. Second point is the structurization and visualization of design space using data mining. Third point is the application to practical problems. In the present study, the influence of the seven pure and hybrid optimizers for design information has been investigated in order to explain the selection manner of optimizer for data mining. A single-stage hybrid rocket design problem is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In the present study, the evolutionary hybrid optimisation methodology between DE and GA is employed. It was confirmed that this methodology had the high performance regarding the convergence and diversity, as well as the strength for noise (Chiba, 2013). Note that noise imitates the error on computational analyses and experiments and is described as the perturbation on objective functions.…”
Section: Optimisation Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…In the present study, the evolutionary hybrid optimisation methodology between DE and GA is employed. It was confirmed that this methodology had the high performance regarding the convergence and diversity, as well as the strength for noise (Chiba, 2013). Note that noise imitates the error on computational analyses and experiments and is described as the perturbation on objective functions.…”
Section: Optimisation Methodsmentioning
confidence: 58%
“…In addition, since the designers require to present many exact optimum solutions for the decision of a compromise one, an evolutionary-based Pareto approach as an efficient multi-thread algorithm, which the plural individuals are parallel conducted, is employed instead of gradient-based methods. The optimiser used in the present study is the hybrid evolutionary method between the differential evolution (DE) and the genetic algorithm (GA) (Chiba, 2013). Moreover, global design information is primarily essential in order to determine a compromise solution.…”
Section: Optimisation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the evolutionary hybrid optimization methodology between DE and GA is employed. It was confirmed that this methodology had the high performance regarding the convergence and diversity, as well as the strength for noise [11]. Note that noise imitates the error on computational analyses and experiments and is described as the perturbation on objective functions.…”
Section: Hybrid Optimizermentioning
confidence: 58%
“…In addition, since the designers require to present many exact optimum solutions for the decision of a compromise one, an evolutionary-based Pareto approach as an efficient multi-thread algorithm, which the plural individuals are parallel conducted, is employed instead of gradient-based methods. The optimizer used in the present study is the evolutionary hybrid method between the differential evolution (DE) and the genetic algorithm (GA) [11]. Moreover, global design information is primarily essential in order to determine a compromise solution.…”
Section: Journal Of Space Engineeringmentioning
confidence: 99%